Community-based participatory research to improve primary mental health services - Muhlisin, Abi; Pratiwi, Arum (International Journal of Research in Medical Sciences, 2017)
Background: Global statistics show that mental illness is among the three most common diseases globally: about 12% to 15% of the global population suffer from mental illness, this is a rate higher than heart disease and disability and twice as high as cancer. The objective of this study was to improve public health conditions through community involvement and social action that is mental health worker knowledge and skill. Methods: A purposive sampling of communities was undertaken in a village of Indonesia. The numbers of participants were trained about knowledge and skill as a mental health workers, then selected 15 people who have the best score and the most capable. Level of knowledge and skill were measured sequent for three times using multiple choice test questions. Periodic analysis used repeated measure ANOVA. Results: There were differences of mental health worker knowledge of each period. The differences between the mental health workers’ knowledge in each period is shown by a test of between-subjects effect to have an F score of 189.476 with a P value of 0.00; and the most remarkable improvement in knowledge as after given skill training in Wilk lambda of 248.71 by P value 0.00. Conclusions: There were differences of mental health worker knowledge of each period. The differences between the mental health workers’ knowledge in each period is shown by a test of between-subjects effect to have an F score of 189.476 with a P value of 0.00; and the most remarkable improvement in knowledge as after given skill training in Wilk lambda of 248.71 by P value 0.00.